Precise timing and recent advancements with segmented anode PICOSEC Micromegas prototypes. (1st October 2022) - ,; Manthos, I.; Aune, S.; Bortfeldt, J.; Brunbauer, F.; David, C.; Desforge, D.; Fanourakis, G.; Gallinaro, M.; García, F.; Giomataris, I.; Gustavsson, T.; et al.
Abstract: Timing information in current and future accelerator facilities is important for resolving objects (particle tracks, showers, etc.) in extreme large particles multiplicities on the detection systems. The PICOSEC Micromegas detector has demonstrated the ability to time 150 GeV muons with a sub-25 ps precision. Driven by detailed simulation studies and a phenomenological model which describes stochastically the dynamics of the signal formation, new PICOSEC designs were developed that significantly improve the timing performance of the detector. PICOSEC prototypes with reduced drift gap size (∼119 µm) achieved a resolution of 45 ps in timing single photons in laser beam tests (in comparison to 76 ps of the standard PICOSEC detector). Towards large area detectors, multi-pad PICOSEC prototypes with segmented anodes has been developed and studied. Extensive tests in particle beams revealed that the multi-pad PICOSEC technology provides also very precise timing, even when the induced signal is shared among several neighbouring pads. Furthermore, new signal processing algorithms have been developed, which can be applied during data acquisition and provide real time, precise timing.